2003
DOI: 10.1046/j.1467-8624.2003.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Visual Short‐Term Memory Capacity in Infants

Abstract: Four experiments assessed visual short-term memory capacity in 4- to 13-month-old infants by comparing their looking to changing and nonchanging stimulus streams presented side by side. In each stream, 1 to 6 colored squares repeatedly appeared and disappeared. In changing streams, the color of a different randomly chosen square changed each time the display reappeared; the colors remained the same in nonchanging streams. Infants should look longer at changing streams, but only if they can remember the colors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
381
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 303 publications
(420 citation statements)
references
References 58 publications
24
381
6
Order By: Relevance
“…Vogel, Woodman, & Luck, 2001). Many experiments suggest that the infant system cannot hold any more than 3 individuals in parallel (Feigenson & Carey, 2003, 2005Feigenson et al, 2002), though one group of researcher has found that it too can hold up to 4 (Ross-Sheehy, Oakes, & Luck, 2003). Importantly, unlike the analog Early in their third year, English-learning children learn to recite the count list in the standard order (i.e.…”
Section: Prelinguistic Number Representations: Analog Magnitudes Parmentioning
confidence: 99%
“…Vogel, Woodman, & Luck, 2001). Many experiments suggest that the infant system cannot hold any more than 3 individuals in parallel (Feigenson & Carey, 2003, 2005Feigenson et al, 2002), though one group of researcher has found that it too can hold up to 4 (Ross-Sheehy, Oakes, & Luck, 2003). Importantly, unlike the analog Early in their third year, English-learning children learn to recite the count list in the standard order (i.e.…”
Section: Prelinguistic Number Representations: Analog Magnitudes Parmentioning
confidence: 99%
“…This ability may better surface when simple events reduce the difficulty of representing future states of affairs. Because infants can represent objects within the subitizing range (9) and bind them into sets (10,11), encompassing three to four objects (12), we explored the hypothesis that at least within this limit they can also make predictions about the likelihood of future events without prior exposure to their actual frequency. We presented movies in which three identical objects and one different in color and shape bounced randomly inside a container with an open pipe at its base, as in a lottery game [supporting information (SI) Movies 1 and 2].…”
Section: Current Researchmentioning
confidence: 99%
“…Others, however, suggested that a third area, probably in the posterior, superior parietal cortex, needs to be activated that binds both motion and shape processing areas (Zeki, 2001). This (temporary) binding between shape and motion may be related to attention or spatial processing, and which may have a different developmental time course (Oakes et al, 2006;Rentschler et al, 2004;Ross-Sheehy et al, 2003). Thus, it remains unknown to what extend neural development of SFM processing depends on both the development of motion processing related areas and areas that are not directly related to shape or motion processing.…”
Section: Introductionmentioning
confidence: 99%